(3eYQGL GdfHj Udi Gddg Ydjg hSde QhGjI GHf YHGSs - (3GdbQTj GdgGTej, GHf YHGS, YHO Gddg Hf YHGS Hf YHO GdeWdH, J(B68(3g`s
(3ChdgG (B:s
(3bGd Gddg JYGdi (B{(3SHMGf GdPj CSQi HYHOg djdG ef GdeSLO GdMQGe Edi GdeSLO GdCbUi GdPj HGQcfG MhdgbGd GHf YHGS QVj Gddg YfgeG HjfeG GdfHj Udi Gddg Ydjg hSde aj HjJ Ce gGfFs
(3BNQgG (B:s
(3fGbU GdBNQhBNQg EYdGe GdeDefjf hYHO Gddg MJi CJGg Gdjbjf Gddge CMjfG Ydi GdcJGH hGdSfI hGLYdfG HYOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 95s
(3eYLe GdeDdajf(B: 2 / 249s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs